Positron Interactions with Atoms and Ions (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2014)
Dirac, in 1928, combining the ideas of quantum mechanics and the ideas of relativity invented the well-known relativistic wave equation. In his formulation, he predicted an antiparticle of the electron of spin Ä§/2. He thought that this particle must be a proton. Dirac [1] published his interpretation in a paper `A theory of electrons and protons'. It was shown later by the mathematician Hermann Weyl [see Ref. 2] that the Dirac theory was completely symmetric between negative and positive particles and the positive particle must have the same mass as that of the electron. In his J. Robert Oppenheimer Memorial Prize Acceptance Speech, Dirac [2] notes that ‘Blackett was really the first person to obtain hard evidence for the existence of a positron but he was afraid to publish it. He wanted confirmation, he was really over cautious.' Positron, produced by the collision of cosmic rays in a cloud chamber, was detected experimentally by Anderson [3] in 1932. His paper was published in Physical Review in 1933. The concept of the positron and its detection were the important discoveries of the 20th century.